The role of artificial intelligence technologies in expediting financial inclusion: the case of selected African countries - Maouloud, Vatimetou Mokhtar; Adam Sa'ad, Auwal; Kassim, Salina; Abdullah Othman, Anwar Hasan (IIUM Press, 2022)
Artificial intelligence (AI) is a revolutionary technology that has been used tremendously in the contemporary industrial revolution 4.0 technology. AI has played a crucial role in accelerating the financial inclusion rate by easing the use of financial products. From the African perspective, there is a very few notable uses of AI technologies in the banking and finance industry, but such uses are not advanced in nature. Therefore, this paper attempts to study the role of AI for financial inclusion in some selected African countries. This paper is a conceptual study that uses a systematic literature review of 11 recent published papers about the relationship between AI and financial inclusion in the context of Africa. This study uses various and most recent published papers obtained from different online databases (mainly Scopus, Emerald, Elsevier, Tailor & Francis, Springer, EBSCO, and JSTOR) to investigate the conceptual and empirical role of AI on financial inclusion and poverty in some selected African countries. The study reveals that mobile money and crowdfunding are the most common fintech tools used in Africa. Therefore, some recommendations are provided for governments and policymakers to instigate techniques that will enhance digital financial inclusion, including using Artificial Intelligence for poverty alleviation in Africa.